Impact of the nanoparticle incorporation in enhancing mechanical properties of polymers - Hammad Ali; Sajjad Ali; Kashif Ali; Saif Ullah; Pir Muhammad Ismail; Muhammad Humayun; Chao Zeng (Results in Engineering, 2025)
Polymer materials are extensively utilized in various applications due to their versatility and ease of fabrication. However, their inherent mechanical properties often constrain them from being utilized in high performance applications. Thus, incorporating various nanoparticles (NPs) to polymer matrices offers a new approach to overcome their limitations and promote their mechanical properties such as toughness, impact strength, modulus, and tensile strength. This review offers a comprehensive overview of the effect of various types of NPs i.e., carbon-based, ceramics, layered, hybrids, and natural fibers. The detail about reinforcement processes are critically discussed with a focus on an influence of NP dispersions, interfacial contacts, and aspect ratio to achieve the best mechanical improvement. This review further describes the current approaches of evaluating mechanical properties, outlines the potential uses of polymer nanocomposites, and presents the future research directions aiming to improve large-scale fabrication, uniformly dispersing the NPs, and developing multi-use smart materials.